Penerapan Terapi Bermain Mewarnai Gambar Untuk Menurunkan Tingkat Kecemasan Pada Anak Usia Prasekolah Yang Mengalami Hospitalisasi Di RS TK.II.04.05.01 Dr.Soedjono Magelang - Erni Suprapti; Yuni Astuti (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Children are the younger generation who have an important role in maintaining and continuing the ideals of the nation. Several cases of serious health complaints experienced by children require more than just outpatient treatment. If a child is hospitalized, then the child will easily experience a crisis because the child experiences anxiety due to the changes he is experiencing. Children need media that can overcome anxiety due to hospitalization and be able to work with health workers while in treatment. One of the media so that children can overcome anxiety is the skill of playing coloring pictures. Intervention play therapy coloring pictures is done 15-20 minutes every day for 2 days in a row. The level of anxiety before being given play therapy coloring pictures in subject I was 11 (severe anxiety) and subject II was 6 (moderate anxiety). The level of anxiety after being given play therapy coloring pictures in subject I is a score of 9 (moderate anxiety) and subject II a score of 4 (mild anxiety). The conclusion from the discussion of this case study is that there is a decrease in anxiety levels after the application of coloring pictures play therapy in preschool-aged children.